Ensuring Competitiveness in the Agricultural Sector through Innovative Technologies and the Agrologistics System - Juraev, Sh. (American Journal of Biodiversity, 2025)
This article analyzes the importance of introducing innovative technologies and developing the agrologistics system in ensuring competitiveness in agriculture. Using examples from global experience and national reforms, the paper examines factors that contribute to forming a complete value chain in the agricultural sector, improving product quality, expanding export potential, and positively impacting the well-being of the local population.